IMPROVING STUDENTS’S READING COMPREHENSION BY USING SEMANTIC MAPPING - SINAGA, LIDIA (Widya Wacana: Jurnal Ilmiah, 2017)
ABSTRACTThe objectives of this research are as follows:   1)to find out whether Semantic mapping can improve student’s reading comprehension at SMP N 7 Surakarta . 2 )To find out how semantic mapping can improve motivation student’s reading comprehension at SMPN 7 Surakarta at the eighth grade students especially class 8 C of SMP Negeri 7 Surakarta in the academic year of 2017/2018. In this research the researcher used qualitative and quantitative methods. The qualitative method consisted  of  observation,  interview,and  documentation.  While  the  quantitative  method  was  the calculating the mean score of the pre-test, post-test 1, and post-test 2.   The result of this research showed that semantic mapping could improve the students’reading comprehension at the eighth grade students especially class 8 C of SMP Negeri 7 Surakarta. The improvement could be seen from the result of the test. The mean score of pre-test was 61,00, post-test 1 was 71,56 and post-test 2 was 80,06. Moreover, the result of t-test was 12,38 in cycle 1 and 15,49 in cycle 2. It meant that there was improvement in students’ reading comprehension.Keywords: Classroom Action Research, Students’Reading Comprehension, Semantic Mapping. ABSTRAKTujuan dari penelitian ini adalah sebagai berikut: 1) untuk mengetahui apakah pemetaan Semantic dapat meningkatkan pemahaman membaca siswa di SMP N 7 Surakarta. 2) Untuk mengetahui bagaimana pemetaan semantik dapat meningkatkan motivasi pemahaman membaca siswa di SMPN 7 Surakarta pada siswa kelas delapan khususnya kelas 8 C SMP Negeri 7 Surakarta pada tahun akademik 2017/2018. Dalam penelitian ini peneliti menggunakan metode kualitatif dan kuantitatif. Metode kualitatif terdiri dari observasi, wawancara, dan dokumentasi. Sedangkan metode kuantitatif adalah menghitung skor rata-rata pre-test, post-test 1, dan post-test 2. Hasil penelitian ini menunjukkan bahwa pemetaan semantik dapat meningkatkan pemahaman siswa pada siswa kelas delapan khususnya kelas 8 C SMP Negeri 7 Surakarta. Peningkatan itu bisa dilihat dari hasil tes. Nilai rata-rata pre-test adalah 61,00, post-test 1 adalah 71,56 dan post-test 2 adalah 80,06. Selain itu, hasil uji-t adalah 12,38 pada siklus 1 dan 15,49 pada siklus 2. Ini berarti bahwa ada peningkatan dalam pemahaman membaca siswa..Kata kunci: Penelitian Tindakan Kelas, Pemahaman Siswa, Pemetaan Semantik.